The Effect of Green Marketing and Green Product Implementation on Ecobag Purchasing Decisions at Goodiebag.del Medan - Tiffanny Calista Susanto; Ihdina Gustina; Muammar Rinaldi (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2023)
People’s daily activities are inseparable from the use of plastic bags, from supermarkets to small shops, all of them use a plastic bag as a means of storing groceries. Then the remaining use of plastic bags is what causes long-terms damage to the ecosystem and the surrounding natural environment. Because plastic waste is classified as difficult to decompose and if it continues to be sustainable towards the accumulation of plastic waste, it is feared that it will cause air pollution and damage to the surrounding marine ecosystem. This study used quantitative methods and the purpose of this study is to see purchasing decisions through the implementation of green marketing and green products. This study collected data through questionnaire techniques that were distributed to consumers measured by Likert scale and the sampling technique used is saturated sampling. The results showed that green marketing and green products have a significant influence on purchasing decisions.